The Role of Hot Spot Analysis in Crime Analysis - Mátyás, Szabolcs (Magyar Rendészet, 2018)
Hot spot analysis is a lesser known method of criminal analysis in our country. Unfortunately, in the everyday police work it is not used frequently and even the criminologists and criminal geographers look at this method as an adopted child. It is hard to say why Hungarian experts averse to it, since even in our country the right GIS softwares are available and one does not need any indepth knowledge to be able to use these computer programmes. The above mentioned is further underlined by the fact that there are hardly any studies on hot spot analysis in Hungarian which can be used in practice. It is a similar situation to crime mapping which is also among the wrongly omitted tools, though both of them would be of great help for the everyday police work. The current study wants to introduce the most important notions, research history, map display and analysis possibilities of hotspot analysis.